Methods to Strengthen State Support for the Use of Entrepreneurship in the Development of Handicrafts - Rano Gofurovna, Abdullaeva; Dilshod Abdujabbarovich, Elov; Madina Kamilovna, Abdullaeva (International Journal of Psychosocial Rehabilitation, 2020)
National handicrafts play an important role in the development of small business and private entrepreneurship in the national economy. The scientific article covers topical issues of the development of entrepreneurship based on national crafts.